PENGARUH LITERASI DIGITAL MAHASISWA, PENDAMPINGAN MAHASISWA, DAN KOMPETENSI TEKNOLOGI UMKM TERHADAP TRANSFORMASI DIGITAL UMKM DI KOTA PALEMBANG DENGAN ADOPSI TEKNOLOGI SEBAGAI VARIABEL MEDIASI - Maulana; Nopa Dwi Saputra (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
Digital transformation is a strategic necessity for MSMEs in Palembang City to increase competitiveness in the digital economy era. As digital natives, students possess digital literacy and mentoring skills that can accelerate the digitalization process of MSMEs. This study aims to analyze the influence of student digital literacy, student mentoring, and MSME technological competence on digital transformation, with digital technology adoption as a mediating variable. A quantitative approach was used through a survey of 150 student MSME mentors and 80 MSME owners. The research instrument used a Likert scale, and data analysis was conducted using Structural Equation Modeling (SEM-PLS) to test the direct and indirect effects between variables. The results show that student digital literacy, student mentoring, and MSME technological competence have a significant positive effect on digital technology adoption, while technology adoption has a significant effect on MSME digital transformation. Technology adoption also significantly mediates the relationship between the three independent variables and MSME digital transformation. The research model produced an R² value of 0.57, indicating that 57% of the variation in MSME digital transformation can be explained by the variables in the model. These findings underscore the importance of collaboration between students and MSMEs in accelerating technology adoption and the need to strengthen digital-based mentoring programs by local governments and universities